2018
DOI: 10.1002/bit.26600
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a membrane‐separated and a membrane‐less electrobioreactor for bioelectrochemical syntheses

Abstract: Bioelectrochemical systems (BESs) have the potential to contribute to the energy revolution driven by the new bio-economy. Until recently, simple reactor designs with minimal process analytics have been used. In recent years, assemblies to host electrodes in bioreactors have been developed resulting in so-called "electrobioreactors." Bioreactors are scalable, well-mixed, controlled, and therefore widely used in biotechnology and adding an electrode extends the possibilities to investigate bioelectrochemical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…This has been shown for the production of para‐hydroxybenzoate in a single chamber reactor with up to 2.5 L working volume , for current production in a single chamber system with 2.5 L , for current production in a two chamber electro‐stirred tank reactor with up to two liter and for the production of organic acids in a two chamber reactor with up to 2 l . It has also been shown that CFD (Computational Fluid Dynamics) studies for the “upgraded” bioreactors reveal the mixing conditions within the reactor, so it might be possible to use the knowledge gained from CFD simulations for the scale up of the systems . Recently, developed a single‐chamber BES with a rode‐shaped “All‐in‐One” electrolysis electrode which can be easily inserted into typical bioreactors (e.g.…”
Section: Scale Up In Electrobiotechnologymentioning
confidence: 98%
See 1 more Smart Citation
“…This has been shown for the production of para‐hydroxybenzoate in a single chamber reactor with up to 2.5 L working volume , for current production in a single chamber system with 2.5 L , for current production in a two chamber electro‐stirred tank reactor with up to two liter and for the production of organic acids in a two chamber reactor with up to 2 l . It has also been shown that CFD (Computational Fluid Dynamics) studies for the “upgraded” bioreactors reveal the mixing conditions within the reactor, so it might be possible to use the knowledge gained from CFD simulations for the scale up of the systems . Recently, developed a single‐chamber BES with a rode‐shaped “All‐in‐One” electrolysis electrode which can be easily inserted into typical bioreactors (e.g.…”
Section: Scale Up In Electrobiotechnologymentioning
confidence: 98%
“…On the contrary, it is necessary to also maintain the flow regime within the cell, giving reason for the use of rational scale up methods . Rational scale up in electrobiotechnology to a larger scale has not been shown so far, but several suggestions for scale up parameters have been made, including the calculation of dimensionless numbers, geometrical similarity, model‐based approaches such as computational fluid dynamics and electrode surface area .…”
Section: Scale Up In Electrobiotechnologymentioning
confidence: 99%
“…Microbial fuel cells are still in the spotlight of academic research; however, a rising number of publications is dealing with the industrial implementation such as scale‐up approaches of electrochemical bioreactors or the implementation of MFCs into WWTPs , . It can be stated, that MFCs are an emerging and economical technology that combines wastewater treatment and current generation.…”
Section: Removal Of Organics and Micropollutantsmentioning
confidence: 99%
“…add electrochemical control to the system while at the same time being able to use the existing infrastructure of the commercial bioreactor allowing a define controlled fermentation process (Figure 11). 154 The assembly was made of PEEK and designed and manufactured to host the working and Identical fittings were used to contact the working and counter electrode by integration of a glass cylinder (d=6 mm) with a platinum wire (d=0.5 mm, manufactured from Fischer Labortechnik GmbH, Frankfurt am Main, Germany) melted into the glass cylinder. The scaled-up reactor was operated and inoculated in the same manner as described above in the experiments using 350 mL custom-made electrobioreactors.…”
Section: Bes Set-up and Operationmentioning
confidence: 99%
“…Sulfuric acid (5 mM) was used as mobile phase with a flow rate of 0.6 mL min -1 at 60 °C over a total run time of 30 min. Quantification was done using a calibration curve with external standards in the range of 0 to 200 mM lactate, succinate and acetate, respectively 154. Lysine and alanine were analyzed on an equivalent HPLC system equipped with a Kinetex® 2.6 µm XB-C18 100 Å 30x2.1 mm column (Phenomenex, Aschaffenburg, Germany) and coupled to a triplequadrupole mass spectrometer (LCMS-8040, Shimadzu Deutschland GmbH, Duisburg, Germany) with an electrospray ionization source (Shimadzu Deutschland GmbH, Duisburg, Germany).…”
mentioning
confidence: 99%